FAMILY’S ROLE AND LEARNING ACHIEVEMENT OF ELEMENTARY SCHOOL’S AGE CHILDREN - Mita Apriyanti; Anika Candrasari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The academic demands for students are getting higher. In addition, home is the first growth‟s place besides the school. Families with affection, parenting pattern creates an environment that suitable for brain development, in which the family has a great influence on the learning process of children. Family members, especially mother, plays a big role in children‟s growth. The research‟s aim was to analyze the correlation between mother‟s perception about family‟s role and learning achievement of the children. It was analytical observational study with cross sectional approach and purposive sampling technique.Sample used 70 mothers and children who had met the criteria for restriction. Questionnaires and academic values were used as a measuring tool. Data analysis used Spearman correlation statistical test SPSS 18.0 for windows. From the data, it showed that there was no correlation between mother's perception and learning achievement of elementary school‟s age children with p> 0,05. The conclusion of this study was the learning achievement of the children was not only determined by the mother's perception factor but also determined by many factors. Parent‟s education, occupation, family‟s incomeand facilities at home affected the learning achievements of children. Keyword: mother‟s perception, family‟s role, learning achievement, children, elementary school